Geographic distribution and genetic compatibility among six karyotypic forms of Anopheles peditaeniatus (Diptera: Culicidae) in Thailand - Saeung A. (2014)
Fifty-three isolines of Anopheles peditaeniatus were established from individual wild-caught females collected from cow-baited traps in 17 provinces of Thailand. Three types of X (X 1, X 2, X 3) and 6 types of Y (Y 1,Y 2, Y 3, Y 4, Y 5, Y 6) chromosomes were determined based on different amounts of major block(s) of heterochromatin. These sex chromosomes comprised 6 karyotypic forms designated as Forms A (X 3, Y 1), B (X 1, X 2, X 3, Y 2), C (X 3, Y 3), D (X 1, X 2, X 3, Y 4), E (X 1, X 2, X 3,Y 5) and F (X 2, X 3, Y 6). Form F is a new metaphase karyotype discovered in this study and is commonly found in all regions. Form A was found only in Lampang province, whereas Form E is widespread throughout the country. Forms B, C and D were obtained from the northern, northeastern, western and southern regions. Crossing experiments among the 11 isoline colonies representing the 6 karyotypic forms of An. peditaeniatus indicated genetic compatibility yielding viable progenies and complete synapsis of salivary gland polytene chromosomes through to the F 2-generations. The results suggested the conspecific nature of these karyotypic forms which were further supported by very low intraspecific variation (genetic distance = 0.000-0.003) of nucleotide sequences in ribosomal DNA (ITS2) and mitochondrial DNA (COI and COII).